Ambiguity of definition of substitution in lambda calculus












1












$begingroup$


From Type Theory and Formal Proof, An Introduction by Rob Nederpelt and Herman Geuvers:



Definition 1.6.1 (Substitution)



(1a) $x[x := N] equiv N$,



(1b) $y[x := N] equiv y$ if $x not equiv y$,



(2) $(PQ)[x := N] equiv (P[x := N])(Q[x := N])$,



(3) $(lambda y . P)[x := N] equiv lambda z . (P^{y to z} [x := N])$, if $lambda z . P^{y to z}$ is an $alpha$-variant of $lambda y . P$ such that $z notin FV(N)$.



If I look at $(lambda y . y)[y := a]$ then it seems that I can have either:



$(lambda y . y)[y := a] = lambda y . (y[y := a]) = lambda y . a$



or



$(lambda y . y)[y := a] = lambda z . (z[y := a]) = lambda z . z$



These are very different. Have I missed something in the definition?










share|cite|improve this question









$endgroup$












  • $begingroup$
    Maybe (3) is missing the condition that you should have $z notequiv x$ which would invalidate the first substitution? (Not sure, not being completely familiar with the notation being used here - but the first result is definitely the suspect one.)
    $endgroup$
    – Daniel Schepler
    Dec 19 '18 at 23:20












  • $begingroup$
    The wikipedia definition seems to differ from this one: en.wikipedia.org/wiki/Lambda_calculus#Substitution
    $endgroup$
    – user695931
    Dec 20 '18 at 0:49
















1












$begingroup$


From Type Theory and Formal Proof, An Introduction by Rob Nederpelt and Herman Geuvers:



Definition 1.6.1 (Substitution)



(1a) $x[x := N] equiv N$,



(1b) $y[x := N] equiv y$ if $x not equiv y$,



(2) $(PQ)[x := N] equiv (P[x := N])(Q[x := N])$,



(3) $(lambda y . P)[x := N] equiv lambda z . (P^{y to z} [x := N])$, if $lambda z . P^{y to z}$ is an $alpha$-variant of $lambda y . P$ such that $z notin FV(N)$.



If I look at $(lambda y . y)[y := a]$ then it seems that I can have either:



$(lambda y . y)[y := a] = lambda y . (y[y := a]) = lambda y . a$



or



$(lambda y . y)[y := a] = lambda z . (z[y := a]) = lambda z . z$



These are very different. Have I missed something in the definition?










share|cite|improve this question









$endgroup$












  • $begingroup$
    Maybe (3) is missing the condition that you should have $z notequiv x$ which would invalidate the first substitution? (Not sure, not being completely familiar with the notation being used here - but the first result is definitely the suspect one.)
    $endgroup$
    – Daniel Schepler
    Dec 19 '18 at 23:20












  • $begingroup$
    The wikipedia definition seems to differ from this one: en.wikipedia.org/wiki/Lambda_calculus#Substitution
    $endgroup$
    – user695931
    Dec 20 '18 at 0:49














1












1








1





$begingroup$


From Type Theory and Formal Proof, An Introduction by Rob Nederpelt and Herman Geuvers:



Definition 1.6.1 (Substitution)



(1a) $x[x := N] equiv N$,



(1b) $y[x := N] equiv y$ if $x not equiv y$,



(2) $(PQ)[x := N] equiv (P[x := N])(Q[x := N])$,



(3) $(lambda y . P)[x := N] equiv lambda z . (P^{y to z} [x := N])$, if $lambda z . P^{y to z}$ is an $alpha$-variant of $lambda y . P$ such that $z notin FV(N)$.



If I look at $(lambda y . y)[y := a]$ then it seems that I can have either:



$(lambda y . y)[y := a] = lambda y . (y[y := a]) = lambda y . a$



or



$(lambda y . y)[y := a] = lambda z . (z[y := a]) = lambda z . z$



These are very different. Have I missed something in the definition?










share|cite|improve this question









$endgroup$




From Type Theory and Formal Proof, An Introduction by Rob Nederpelt and Herman Geuvers:



Definition 1.6.1 (Substitution)



(1a) $x[x := N] equiv N$,



(1b) $y[x := N] equiv y$ if $x not equiv y$,



(2) $(PQ)[x := N] equiv (P[x := N])(Q[x := N])$,



(3) $(lambda y . P)[x := N] equiv lambda z . (P^{y to z} [x := N])$, if $lambda z . P^{y to z}$ is an $alpha$-variant of $lambda y . P$ such that $z notin FV(N)$.



If I look at $(lambda y . y)[y := a]$ then it seems that I can have either:



$(lambda y . y)[y := a] = lambda y . (y[y := a]) = lambda y . a$



or



$(lambda y . y)[y := a] = lambda z . (z[y := a]) = lambda z . z$



These are very different. Have I missed something in the definition?







lambda-calculus






share|cite|improve this question













share|cite|improve this question











share|cite|improve this question




share|cite|improve this question










asked Dec 19 '18 at 23:09









user695931user695931

17511




17511












  • $begingroup$
    Maybe (3) is missing the condition that you should have $z notequiv x$ which would invalidate the first substitution? (Not sure, not being completely familiar with the notation being used here - but the first result is definitely the suspect one.)
    $endgroup$
    – Daniel Schepler
    Dec 19 '18 at 23:20












  • $begingroup$
    The wikipedia definition seems to differ from this one: en.wikipedia.org/wiki/Lambda_calculus#Substitution
    $endgroup$
    – user695931
    Dec 20 '18 at 0:49


















  • $begingroup$
    Maybe (3) is missing the condition that you should have $z notequiv x$ which would invalidate the first substitution? (Not sure, not being completely familiar with the notation being used here - but the first result is definitely the suspect one.)
    $endgroup$
    – Daniel Schepler
    Dec 19 '18 at 23:20












  • $begingroup$
    The wikipedia definition seems to differ from this one: en.wikipedia.org/wiki/Lambda_calculus#Substitution
    $endgroup$
    – user695931
    Dec 20 '18 at 0:49
















$begingroup$
Maybe (3) is missing the condition that you should have $z notequiv x$ which would invalidate the first substitution? (Not sure, not being completely familiar with the notation being used here - but the first result is definitely the suspect one.)
$endgroup$
– Daniel Schepler
Dec 19 '18 at 23:20






$begingroup$
Maybe (3) is missing the condition that you should have $z notequiv x$ which would invalidate the first substitution? (Not sure, not being completely familiar with the notation being used here - but the first result is definitely the suspect one.)
$endgroup$
– Daniel Schepler
Dec 19 '18 at 23:20














$begingroup$
The wikipedia definition seems to differ from this one: en.wikipedia.org/wiki/Lambda_calculus#Substitution
$endgroup$
– user695931
Dec 20 '18 at 0:49




$begingroup$
The wikipedia definition seems to differ from this one: en.wikipedia.org/wiki/Lambda_calculus#Substitution
$endgroup$
– user695931
Dec 20 '18 at 0:49










1 Answer
1






active

oldest

votes


















1












$begingroup$

Clearly, $lambda y. a$ and $lambda z.z$ are different (in the sense of not $alpha$-equivalent) terms.



Actually, $(lambda y. y)[y := a] = lambda z. z = lambda y. y,$ (up to $alpha$-equivalence) and there is no ambiguity.
Indeed, according to definition 1.6.1 in Nederpelt' and Geuvers' handbook, $(lambda y.y)[y:=a] neq lambda y.(y[y:=a])$ because in general $lambda z . P^{y to z}$ is defined provided that $z notin FV(P)$ (see definition 1.5.1) and this condition does not hold in $lambda y.y$ (where $z = y = P$).






share|cite|improve this answer









$endgroup$













  • $begingroup$
    I thought it would hold by remark 1.6.3 (1)?
    $endgroup$
    – user695931
    Dec 20 '18 at 1:05






  • 1




    $begingroup$
    @user695931 - In Remark 1.6.3 (1) it is implicitly assumed that $x neq y$. Remind the intuitive meaning of substitution (explained just before definition 1.6.1): $M[x := N]$ stands for $M$ in which $N$ has been substituted for the free variable $x$. Clearly, in $M = lambda y. P$ the variable $y$ is bound, so if $x = y$ then $(lambda y.P)[x := N]) = lambda y.P$ (no substitution is performed): this is exactly what happens for $(lambda y.y)[y:=a]$.
    $endgroup$
    – Taroccoesbrocco
    Dec 20 '18 at 9:04












  • $begingroup$
    I guess this makes sense. It seems confusing that they made the condition $x not equiv y$ explicit in 1b, but not here. The wikipedia version seems a bit clearer: en.wikipedia.org/wiki/Lambda_calculus#Substitution
    $endgroup$
    – user695931
    Dec 20 '18 at 15:32












Your Answer





StackExchange.ifUsing("editor", function () {
return StackExchange.using("mathjaxEditing", function () {
StackExchange.MarkdownEditor.creationCallbacks.add(function (editor, postfix) {
StackExchange.mathjaxEditing.prepareWmdForMathJax(editor, postfix, [["$", "$"], ["\\(","\\)"]]);
});
});
}, "mathjax-editing");

StackExchange.ready(function() {
var channelOptions = {
tags: "".split(" "),
id: "69"
};
initTagRenderer("".split(" "), "".split(" "), channelOptions);

StackExchange.using("externalEditor", function() {
// Have to fire editor after snippets, if snippets enabled
if (StackExchange.settings.snippets.snippetsEnabled) {
StackExchange.using("snippets", function() {
createEditor();
});
}
else {
createEditor();
}
});

function createEditor() {
StackExchange.prepareEditor({
heartbeatType: 'answer',
autoActivateHeartbeat: false,
convertImagesToLinks: true,
noModals: true,
showLowRepImageUploadWarning: true,
reputationToPostImages: 10,
bindNavPrevention: true,
postfix: "",
imageUploader: {
brandingHtml: "Powered by u003ca class="icon-imgur-white" href="https://imgur.com/"u003eu003c/au003e",
contentPolicyHtml: "User contributions licensed under u003ca href="https://creativecommons.org/licenses/by-sa/3.0/"u003ecc by-sa 3.0 with attribution requiredu003c/au003e u003ca href="https://stackoverflow.com/legal/content-policy"u003e(content policy)u003c/au003e",
allowUrls: true
},
noCode: true, onDemand: true,
discardSelector: ".discard-answer"
,immediatelyShowMarkdownHelp:true
});


}
});














draft saved

draft discarded


















StackExchange.ready(
function () {
StackExchange.openid.initPostLogin('.new-post-login', 'https%3a%2f%2fmath.stackexchange.com%2fquestions%2f3046968%2fambiguity-of-definition-of-substitution-in-lambda-calculus%23new-answer', 'question_page');
}
);

Post as a guest















Required, but never shown

























1 Answer
1






active

oldest

votes








1 Answer
1






active

oldest

votes









active

oldest

votes






active

oldest

votes









1












$begingroup$

Clearly, $lambda y. a$ and $lambda z.z$ are different (in the sense of not $alpha$-equivalent) terms.



Actually, $(lambda y. y)[y := a] = lambda z. z = lambda y. y,$ (up to $alpha$-equivalence) and there is no ambiguity.
Indeed, according to definition 1.6.1 in Nederpelt' and Geuvers' handbook, $(lambda y.y)[y:=a] neq lambda y.(y[y:=a])$ because in general $lambda z . P^{y to z}$ is defined provided that $z notin FV(P)$ (see definition 1.5.1) and this condition does not hold in $lambda y.y$ (where $z = y = P$).






share|cite|improve this answer









$endgroup$













  • $begingroup$
    I thought it would hold by remark 1.6.3 (1)?
    $endgroup$
    – user695931
    Dec 20 '18 at 1:05






  • 1




    $begingroup$
    @user695931 - In Remark 1.6.3 (1) it is implicitly assumed that $x neq y$. Remind the intuitive meaning of substitution (explained just before definition 1.6.1): $M[x := N]$ stands for $M$ in which $N$ has been substituted for the free variable $x$. Clearly, in $M = lambda y. P$ the variable $y$ is bound, so if $x = y$ then $(lambda y.P)[x := N]) = lambda y.P$ (no substitution is performed): this is exactly what happens for $(lambda y.y)[y:=a]$.
    $endgroup$
    – Taroccoesbrocco
    Dec 20 '18 at 9:04












  • $begingroup$
    I guess this makes sense. It seems confusing that they made the condition $x not equiv y$ explicit in 1b, but not here. The wikipedia version seems a bit clearer: en.wikipedia.org/wiki/Lambda_calculus#Substitution
    $endgroup$
    – user695931
    Dec 20 '18 at 15:32
















1












$begingroup$

Clearly, $lambda y. a$ and $lambda z.z$ are different (in the sense of not $alpha$-equivalent) terms.



Actually, $(lambda y. y)[y := a] = lambda z. z = lambda y. y,$ (up to $alpha$-equivalence) and there is no ambiguity.
Indeed, according to definition 1.6.1 in Nederpelt' and Geuvers' handbook, $(lambda y.y)[y:=a] neq lambda y.(y[y:=a])$ because in general $lambda z . P^{y to z}$ is defined provided that $z notin FV(P)$ (see definition 1.5.1) and this condition does not hold in $lambda y.y$ (where $z = y = P$).






share|cite|improve this answer









$endgroup$













  • $begingroup$
    I thought it would hold by remark 1.6.3 (1)?
    $endgroup$
    – user695931
    Dec 20 '18 at 1:05






  • 1




    $begingroup$
    @user695931 - In Remark 1.6.3 (1) it is implicitly assumed that $x neq y$. Remind the intuitive meaning of substitution (explained just before definition 1.6.1): $M[x := N]$ stands for $M$ in which $N$ has been substituted for the free variable $x$. Clearly, in $M = lambda y. P$ the variable $y$ is bound, so if $x = y$ then $(lambda y.P)[x := N]) = lambda y.P$ (no substitution is performed): this is exactly what happens for $(lambda y.y)[y:=a]$.
    $endgroup$
    – Taroccoesbrocco
    Dec 20 '18 at 9:04












  • $begingroup$
    I guess this makes sense. It seems confusing that they made the condition $x not equiv y$ explicit in 1b, but not here. The wikipedia version seems a bit clearer: en.wikipedia.org/wiki/Lambda_calculus#Substitution
    $endgroup$
    – user695931
    Dec 20 '18 at 15:32














1












1








1





$begingroup$

Clearly, $lambda y. a$ and $lambda z.z$ are different (in the sense of not $alpha$-equivalent) terms.



Actually, $(lambda y. y)[y := a] = lambda z. z = lambda y. y,$ (up to $alpha$-equivalence) and there is no ambiguity.
Indeed, according to definition 1.6.1 in Nederpelt' and Geuvers' handbook, $(lambda y.y)[y:=a] neq lambda y.(y[y:=a])$ because in general $lambda z . P^{y to z}$ is defined provided that $z notin FV(P)$ (see definition 1.5.1) and this condition does not hold in $lambda y.y$ (where $z = y = P$).






share|cite|improve this answer









$endgroup$



Clearly, $lambda y. a$ and $lambda z.z$ are different (in the sense of not $alpha$-equivalent) terms.



Actually, $(lambda y. y)[y := a] = lambda z. z = lambda y. y,$ (up to $alpha$-equivalence) and there is no ambiguity.
Indeed, according to definition 1.6.1 in Nederpelt' and Geuvers' handbook, $(lambda y.y)[y:=a] neq lambda y.(y[y:=a])$ because in general $lambda z . P^{y to z}$ is defined provided that $z notin FV(P)$ (see definition 1.5.1) and this condition does not hold in $lambda y.y$ (where $z = y = P$).







share|cite|improve this answer












share|cite|improve this answer



share|cite|improve this answer










answered Dec 19 '18 at 23:28









TaroccoesbroccoTaroccoesbrocco

5,77971840




5,77971840












  • $begingroup$
    I thought it would hold by remark 1.6.3 (1)?
    $endgroup$
    – user695931
    Dec 20 '18 at 1:05






  • 1




    $begingroup$
    @user695931 - In Remark 1.6.3 (1) it is implicitly assumed that $x neq y$. Remind the intuitive meaning of substitution (explained just before definition 1.6.1): $M[x := N]$ stands for $M$ in which $N$ has been substituted for the free variable $x$. Clearly, in $M = lambda y. P$ the variable $y$ is bound, so if $x = y$ then $(lambda y.P)[x := N]) = lambda y.P$ (no substitution is performed): this is exactly what happens for $(lambda y.y)[y:=a]$.
    $endgroup$
    – Taroccoesbrocco
    Dec 20 '18 at 9:04












  • $begingroup$
    I guess this makes sense. It seems confusing that they made the condition $x not equiv y$ explicit in 1b, but not here. The wikipedia version seems a bit clearer: en.wikipedia.org/wiki/Lambda_calculus#Substitution
    $endgroup$
    – user695931
    Dec 20 '18 at 15:32


















  • $begingroup$
    I thought it would hold by remark 1.6.3 (1)?
    $endgroup$
    – user695931
    Dec 20 '18 at 1:05






  • 1




    $begingroup$
    @user695931 - In Remark 1.6.3 (1) it is implicitly assumed that $x neq y$. Remind the intuitive meaning of substitution (explained just before definition 1.6.1): $M[x := N]$ stands for $M$ in which $N$ has been substituted for the free variable $x$. Clearly, in $M = lambda y. P$ the variable $y$ is bound, so if $x = y$ then $(lambda y.P)[x := N]) = lambda y.P$ (no substitution is performed): this is exactly what happens for $(lambda y.y)[y:=a]$.
    $endgroup$
    – Taroccoesbrocco
    Dec 20 '18 at 9:04












  • $begingroup$
    I guess this makes sense. It seems confusing that they made the condition $x not equiv y$ explicit in 1b, but not here. The wikipedia version seems a bit clearer: en.wikipedia.org/wiki/Lambda_calculus#Substitution
    $endgroup$
    – user695931
    Dec 20 '18 at 15:32
















$begingroup$
I thought it would hold by remark 1.6.3 (1)?
$endgroup$
– user695931
Dec 20 '18 at 1:05




$begingroup$
I thought it would hold by remark 1.6.3 (1)?
$endgroup$
– user695931
Dec 20 '18 at 1:05




1




1




$begingroup$
@user695931 - In Remark 1.6.3 (1) it is implicitly assumed that $x neq y$. Remind the intuitive meaning of substitution (explained just before definition 1.6.1): $M[x := N]$ stands for $M$ in which $N$ has been substituted for the free variable $x$. Clearly, in $M = lambda y. P$ the variable $y$ is bound, so if $x = y$ then $(lambda y.P)[x := N]) = lambda y.P$ (no substitution is performed): this is exactly what happens for $(lambda y.y)[y:=a]$.
$endgroup$
– Taroccoesbrocco
Dec 20 '18 at 9:04






$begingroup$
@user695931 - In Remark 1.6.3 (1) it is implicitly assumed that $x neq y$. Remind the intuitive meaning of substitution (explained just before definition 1.6.1): $M[x := N]$ stands for $M$ in which $N$ has been substituted for the free variable $x$. Clearly, in $M = lambda y. P$ the variable $y$ is bound, so if $x = y$ then $(lambda y.P)[x := N]) = lambda y.P$ (no substitution is performed): this is exactly what happens for $(lambda y.y)[y:=a]$.
$endgroup$
– Taroccoesbrocco
Dec 20 '18 at 9:04














$begingroup$
I guess this makes sense. It seems confusing that they made the condition $x not equiv y$ explicit in 1b, but not here. The wikipedia version seems a bit clearer: en.wikipedia.org/wiki/Lambda_calculus#Substitution
$endgroup$
– user695931
Dec 20 '18 at 15:32




$begingroup$
I guess this makes sense. It seems confusing that they made the condition $x not equiv y$ explicit in 1b, but not here. The wikipedia version seems a bit clearer: en.wikipedia.org/wiki/Lambda_calculus#Substitution
$endgroup$
– user695931
Dec 20 '18 at 15:32


















draft saved

draft discarded




















































Thanks for contributing an answer to Mathematics Stack Exchange!


  • Please be sure to answer the question. Provide details and share your research!

But avoid



  • Asking for help, clarification, or responding to other answers.

  • Making statements based on opinion; back them up with references or personal experience.


Use MathJax to format equations. MathJax reference.


To learn more, see our tips on writing great answers.




draft saved


draft discarded














StackExchange.ready(
function () {
StackExchange.openid.initPostLogin('.new-post-login', 'https%3a%2f%2fmath.stackexchange.com%2fquestions%2f3046968%2fambiguity-of-definition-of-substitution-in-lambda-calculus%23new-answer', 'question_page');
}
);

Post as a guest















Required, but never shown





















































Required, but never shown














Required, but never shown












Required, but never shown







Required, but never shown

































Required, but never shown














Required, but never shown












Required, but never shown







Required, but never shown







Popular posts from this blog

Plaza Victoria

In PowerPoint, is there a keyboard shortcut for bulleted / numbered list?

How to put 3 figures in Latex with 2 figures side by side and 1 below these side by side images but in...